Fenomena Alih Kode, Campur Kode dalam Penggunaan Unsur Bahasa Jawa dalam Novel Soedirman dan Alfiyah Karya E. Rokajat Asura - Khoirun Nadia; Rintan Amalia Rohar; Tasya Madinah; Callista Azalia Nur Firdaus; Mohammad Afrizal (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Code-switching and code-mixing are linguistic phenomena that reflect the cultural and linguistic diversity of Indonesian society, particularly within literary works. This study aims to analyze how elements of the Javanese language are employed through these phenomena in the novel Soedirman dan Alfiyah by E. Rokajat Asura. Using a literature review method, the study examines relevant theories and previous research on the use of regional languages, specifically Javanese, in literature. The findings reveal that both code-switching and code-mixing enrich character expression, serve as markers of cultural identity, convey emotional depth, and enhance the social messages embedded in the narrative. Visual markers such as italicized text are utilized to distinguish linguistic shifts, although inconsistencies in their application are noted. This research highlights the importance of preserving regional languages in literary works and emphasizes the need for consistent typographical presentation to improve readability and linguistic awareness among readers.